OPTIMALISASI PERAN REMAJA SEBAGAI DUTA PENGGERAK DONOR DARAH MELALUI PROGRAM TEMAN DONOR - Nuraini, Fatia Rizki; Muflikhah, Nina Difla (Universitas Mataram, 2024)
The availability of blood supply remains a crucial issue. But, concerns and lack of public understanding regarding blood donation can pose constraints in achieving the required fulfillment. Teman Donor program was introduced with the aim of inspiring adolescents, particularly high school students in Bojonegoro, to voluntarily participate in blood donation activities. Within the framework of this program, 28 selected adolescents from 9 high schools were engaged as blood donor ambassadors. The process involved several stages: the formation of Teman Donor, socialization and education on blood donation using training modules, forming the official teams of Teman Donor, guidance by the community service team, dissemination of information by Teman Donor through school social networks, and intensive monitoring and evaluation to ensure the effectiveness of the program. Program evaluation using questionnaires indicated an increase in adolescents knowledge and decrease in the level of anxiety and fear towards the blood donation process. A significant proportion, 82.5%, demonstrated good understanding. Furthermore, the majority of participants expressed readiness to blood donation by 87.3%. Through these works, Suggested that participation in blood donation activities can be enhanced and ensuring an adequate supply of blood for medical purposes.